X-ray magnetic circular dichroism studies of III-Mn-V compounds and heterostructures - Wadley, Peter (2012)
This thesis describes the characterisation of GaMnAs, related compounds and heterostructures. GaMnAs and other (III,Mn)V compounds have provided many interesting insights into fundamental physics, and are of considerable potential interest commercially in the field of spintronics. This study examines a set of samples grown by molecular beam epitaxy and characterised using several techniques: primarily this study makes use of the x-ray absorption techniques, x-ray magnetic circular dichroism(XMCD) and x-ray absorption spectroscopy (XAS). In addition, x-ray diffraction (XRD), transport measurements and super conducting quantum interference device (SQUID) magnetometry were used as complimentary techniques.